Blockchain for sustainable e-agriculture: Literature review, architecture for data management, and implications - Dey, Kushankur; Shekhawat, Umedsingh (Journal of cleaner production, 2021)
The architecture design by integrating the blockchain and IoT has gained salience in information systems and information technology research. However, there has not been significant work on the comprehensive and sequential applications of blockchain integrated IoT in e-agriculture for data validation, data storage, data security and data privacy. We aim to bridge this gap in the literature and discuss how the integration of blockchain and IoT can improve backward and forward linkages in agricultural value chains, benefit value chain actors, and augment the performance of IoT network. The study considers use cases of agriculture inputs and commodities/products to demonstrate the application of IoT devices in data collection and blockchain technology for data validation, data storage, data security, and data transmission. RAFT consensus algorithm for permission blockchain and FAIR principles are utilized to make e-agriculture information systems decentralized, efficient, fault tolerant, and interoperable. The technology coupling in e-agriculture can create externalities such as shared benefits, improved coordination between value chain actors, and real-time decision-making for optimal resource allocation and their sustainable utilization in e-agriculture. [Display omitted]